Konsep Kepemimpinan Visioner Di Lingkungan Madrasah Ibtidaiyah - Abd. Rahim Mansyur (Universitas Muslim Indonesia, 2022)
This paper describes the results of theoretical readings on visionary leadership that can be the foundation of leadership in the Ibtidaiyah Madrasah environment. Based on the study material, the analytical approach uses library to research on various literature sources relevant to the study of this writing. Based on the results of the discussion, it can be concluded that visionary leadership is theoretically an ideal leadership pattern that can be applied in The Ibtidaiyah Madrasah environment. This is intended to answer the various complexities of education and learning management problems in the madrasah environment, especially Madrasah Ibtidaiyah. On the other hand, this leadership concept can also provide new insights for the heads of Madrasah Ibtidaiyah so that they can appear as leaders who are more flexible according to the demands of change. Visionary leadership in The Madrasah Ibtidaiyah environment will encourage the orientation of madrasa institutions to the future through the idea of a clear vision. Can make madrasa principals turn their vision into real action through mobilizing all human resources owned and synergized. The application of this leadership can be effective if it is supported by communication patterns and motivation and transparency of all madrasa ecosystems supported by the ability of the madrasa principal to innovate productively. The most substantial thing for the application of this leadership pattern is the adoption of spiritual values that seem to be very much connected to the culture of Madrasah Ibtidaiyah which is based on the Qur'an and Hadith.